Expanding the Spectrum of EBV-positive Marginal Zone Lymphomas: A Lesion Associated With Diverse Immunodeficiency Settings. (October 2018) - Gong, Shunyou; Crane, Genevieve M.; McCall, Chad M.; Xiao, Wenbin; Ganapathi, Karthik A.; Cuka, Nathan; Davies-Hill, Theresa; Xi, Liqiang; Raffeld, Mark; Pittaluga, Stefania; Duffield, Amy S.; Jaffe, Elaine S.
Abstract : Traditionally low-grade B-cell lymphomas have been excluded from the category of monomorphic posttransplant lymphoproliferative disorders. However, recent reports identified Epstein-Barr virus-positive (EBV + ) extranodal marginal zone lymphomas (MZL), almost exclusively seen in the posttransplant setting. Some reported cases responded to reduced immunosuppression, suggesting that they should be considered as a form of posttransplant lymphoproliferative disorders. We identified 10 cases of EBV + MZL, 9 in extranodal sites and 1 presenting in lymph node. Two cases arose following solid organ transplantation, but other settings included iatrogenic immunosuppression for rheumatoid arthritis (2); prior chemotherapy (2); congenital immune deficiency (1); and increased age (3), as the only potential cause of immune dysfunction. There were 4 males and 6 females; age range 18 to 86. The atypical plasmacytoid and/or monocytoid B cells were positive for EBV in all cases, with either latency I or II in all cases tested. Monotypic light chain expression was shown in all with 6 cases positive for IgG, and 2 for IgM, undetermined in 2. Clonal immunoglobulin gene rearrangement was positive in all cases with successful amplification. MYD88 L265P was wild type in the 6 cases tested. We show that EBV + MZLs can arise in a variety of clinical settings, and are most often extranodal. Treatment varied, but most patients had clinically indolent disease with response to reduction of immune suppression, or immunochemotherapy.